THE INCIDENCE OF THE PRINCIPLE OF PROPORTIONALITY IN THE CASE OF PRECAUTIONARY MEASURES ORDERED IN THE ROMANIAN CRIMINAL PROCESS - Alina ANDRESCU (Challenges of the Knowledge Society)
The object of the analysed topic deals with the limits and incidence of the criterion of proportionality in taking, maintaining or terminating insurance measures, offering several procedural remedies. The purpose of the study is to determine some criteria of objectivity and predictability incident to the taking and maintaining of precautionary measures, in order to prevent the abuse of law and the blocking of the use of the patrimony of the person concerned, criteria offered in a set of guarantees of a procedural-criminal nature, the observance of which constitutes a result obligation for the judicial bodies issuing the measure. The author carries out an analysis of the legal content of the protective measures in Romanian criminal procedural law from the perspective of the principles of ensuring the preemption of substantive European law and ensuring European public order, fundamental principles in the European and national normative construction, seeing in this legal order a standard capable of guaranteeing the defense concrete and effective of the rights of the procedural participants, drawing objective boundaries between them, the purpose being to increase the confidence of litigants in the judicial act.